A comparison of the Panama and Nicaragua canal routes - Steuart, William Henry (My University, 1895)
Introduction: Since Cortez sent his report to Charles V of Spain, October 15th 1524 containing a map of the entire Gulf of Mexico showing that a strait did not exist between the Atlantic and Pacific Oceans: the artificial connection of these two oceans has been the dream of the human race. Cortez made a proposition to the king to cut through the mountains. In 1551 Gormara proposed a union of the two oceans by any one of the three routes which engineers of today concede to be the only possible routes. About 1779 two Englishmen Hodgson and Lee secretly surveyed Lake Nicaragua and portions of both coasts. In 1780 Lord Nelson, then a captain, landed two thousand troops in Nicaragua. Lord Nelson said “In order to give facility to the great object of government I intend to possess the Lake of Nicaragua which for the present, may be looked upon as the inland Gibralter of Spanish America, as it commands the only water pass between the oceans its situation must ever render it a principal post to insure passage to the Southern Oceans, and by our possession of it Spanish America is severed into two.” Why is it that these two mighty oceans still roll against the narrow unpierced isthmus s they did when this continent was discovered? Is it because a connection between them is less important to the commercial world of today than it was then?
Citation: Steuart, William Henry. A comparison of the Panama and Nicaragua canal routes. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: History; Panama Canal; Theses; Manuscripts (documents)